Antioxidant and Antimicrobial Activities of Phenolic Compounds Producing from Local Isolate Aspergillus niger - Noor Shukur Ahmed (Journal of Global Pharma Technology, 2016)
The aim of the present research was to examine the phenolic contents; antioxidant and antimicrobial activities of alcoholic extract for Aspergillus niger biomass. The Phenolic compounds were extracted from biomass of isolate by Ethel alcohol, and identified BY using the high performance liquid chromatography analysis (HPLC).  The results were compared with the standard phenolic compounds. This study has found that generally, the biomass extract contains gallic acid, rutin and kampferole. However, the phenolic compounds were extracted by different solvents including: ethyl acetate, methanol and ethanol. The highest concentration of phenolic compounds (264.3.µg/ml) was obtained from the ethanolic extract. Ethanolic extract was screened for antimicrobial activity by using the holes diffusion method against five selected pathogenic bacterial strains which include each of Staphylococcus aureus, Bacillus cereus, Pseudomonase, Escherichia coli, and Klebsella pnuemoniae. We found that compared to G- bacteria, the extract shows high antimicrobial activity against G+ bacteria. On the other hand, Antioxidant activity was determined by measuring the reduction power, and 2, 2-diphenyl-1-picrylhydrazyl radical (DPPH) scavenging activity. Moreover, we found that the antioxidant activity had been maximizing ethanolic biomass extract (106.1, 92) % respectively, while ethyl acetate and methanol extracts (59.5, 10) % and (49.4, 5.5) % respectively.Keywords: Antioxidants, Antimicrobial, DPPH, Reducing power, HPLC, Aspergillus niger.